If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7v = 6 + 6v Solving 7v = 6 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 7v + -6v = 6 + 6v + -6v Combine like terms: 7v + -6v = 1v 1v = 6 + 6v + -6v Combine like terms: 6v + -6v = 0 1v = 6 + 0 1v = 6 Divide each side by '1'. v = 6 Simplifying v = 6
| y=5-2(-2) | | 6[e+5]=9e-5 | | 0.2(x+2)+0.5(x-0.4)=5.44 | | 14x^3-6x^2+35x-15= | | r^2-9r=-8 | | -6-30-8x=40 | | -2(x-6)=3(x+4)-9 | | 6x-15=3(2x-16) | | 8+8x=-22x-22 | | 3(q-5)=13+2r | | 14a+11(24726-14a)=24726 | | -5r+8=6r+8 | | 4x^3+2x+7=0 | | -3y+9=-3y+8 | | 6y+3-y=8 | | 6k=10k-8 | | 2[x(4x+15)+5]=2(x+10) | | 2x-4(4x+8)=38 | | 24x^2-20x+8=0 | | -z-2=4-4z | | v^2+10v-11=0 | | 480=-10(-6x-6) | | 3x+101-4x-33=108-16x-109 | | =3x+3(x+1)+3(x+2) | | -3f-9=-2f | | -14p-3(2-6p)=2(p-2)-6 | | 4x+12-2x=3x-9 | | (x-2)x=224 | | 7y+4x=42 | | 72=1.5x | | a=1.2(h-84) | | 16h-72b=4h-30 |